PENGARUH LATIHAN OPERAN DALAM LINGKARAN TERHADAP KEMAMPUAN PASSING TIM BASKET PUTRA MAN 2 MODEL PEKANBARU - Ahsanul Husna; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, Based on observation of this research aims to determine whether there is influence operant training in a circle on the ability of passing on the boys basketball team MAN 2 Model Pekanbaru with the research methods using pre-test and post test, so as to develop the ability to passing when defensive or at time of attack, specifically pass to the team and get a scored. This research is the experimental treatment (Experimental), the population in this research is the boys basketball team MAN 2 Model Pekanbaru and sample in this research is the whole boys basketball team MAN 2 Model Pekanbaru totaling 12 people. The sampling technique is total sampling. According Arikunto (2006: 134) If the population is less than 100 then it is better taken all. The instruments used in this research is to test individual feed, which aims to measure reaction time foot with stimulation of vision. After that, the data is processed with statistical, normality test with lilifors test at significant level 0,05α. The hypothesis is the influence of exercise circle against passing in passing ability. The data is normal. Based on the analysis of the t test, the results show that the Tcount>Ttable with the value Tcount at 2,705 and Ttable at 1.796. Based on the analysis of statistical data, there are an average Pree-test amounted to 0.285 and the average post-test of 0.239. Thus, there is the influence of exercise on the operands in a circle passing ability in the game of basketball boys team MAN 2 Model Pekanbaru.Keywords: Passing In Circles, Passing